Expanding the shopping cart or improving its contents: A study on “Modern” retail in India - Roy, Devesh; Joshi, Pramod Kumar; Karandikar, Bhushana; Joshi, Shwetima; Sonkar, Vinay Kumar (Walter de Gruyter GmbH, 2014)
Several factors (including rising incomes, urbanization, a young population, and more women in the labor force) have influenced retailing in India in recent years, with the emergence and rapid spread of supermarkets being the most dramatic change. Without disputing the high growth rates of organized retail in the food sector, in this study we test whether supermarket growth is associated with greater demand for nonprice attributes such as food safety and customization of products. Using on-site surveys at supermarkets in three Indian cities of different population sizes and income levels, and using ordered models for consumer choice, we find that nonprice attributes remain subordinate to price for consumers in supermarkets. At the same time, rising import penetration in supermarkets creates an outlet where some consumers can satisfy their demand for nonprice attributes that are not provided by domestic products. The fact that such attributes are not demanded of domestic products and that imports fill in to provide these nonprice attributes implies that demand pull for back-end development is weak in Indian food retail. This is important, because a command approach by the government to induce back-end development will work only if enforcement is strong, which seems unlikely.